1997
DOI: 10.1111/j.2042-3306.1997.tb03120.x
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal surgery in foals: a review of 119 cases (1977–1994)

Abstract: Summary The case records of 119 young horses (all less than age one year) that underwent an exploratory celiotomy during a 17 year period were examined to determine the surgical findings, short‐ and long‐term outcome, and prevalence of small intestinal disease compared to previous reports in the mature horse. Physical and laboratory values were compared for long‐term survivors vs. nonsurvivors and the frequency of post operative intra‐abdominal adhesions was determined. The most common cause for exploratory ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
2
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 14 publications
4
76
2
4
Order By: Relevance
“…Cable et al (20) found a significantly higher survival rate in foals in which the intestines were merely manipulated (79%) compared to foals in which resection was performed (29%). In contrast, Ducharme et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cable et al (20) found a significantly higher survival rate in foals in which the intestines were merely manipulated (79%) compared to foals in which resection was performed (29%). In contrast, Ducharme et al…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive peritonitis is another common complication, although not all adhesions lead to clinical problems (8,20). Peritonitis may be caused by many factors, such as bowel ischaemia, endotoxaemia, contamination during surgery, severe bowel trauma resulting from excessive manipulation during surgery or a leaking anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Betrachtet wurden das Signalement, die Jahreszeit bei Klinikeinweisung, die Diagnose, die chirurgische Therapie, die Operationskomplikationen sowie der Erfolg der chirurgischen Therapie. Vatistas et al 1996, Cable et al 1997, Santschi et al 2000, Thrombotisch-embolische Koliken (Cable et al 1997) und Adhäsionen (Cable et al 1997, Santschi et al 2000 Cable et al (1997) 6 von 119 (5%) Tieren, die während der Operation verstarben. Andere Autoren differenzierten nicht zwischen der Anzahl der verstorbenen und euthanasierten Fohlen (Vatistas et al 1996, Santschi et al 2000, Bartmann et al 2001.…”
Section: Materials Und Methodenunclassified
“…Retrospektive Studien zur Laparotomie des Fohlens existieren im Gegensatz zum erwachsenen Pferd bisher nur wenige , Vatistas et al 1996, Cable et al 1997, Singer und Livesey 1997, Santschi et al 2000, Bartmann et al 2001. Einige Autoren schließen in ihre Betrachtungen nur gastrointestinale Erkrankungen ein , Vatistas et al 1996, Santschi et al 2000.…”
Section: Introductionunclassified
See 1 more Smart Citation